Antithrombotic therapy in patients with atrial fibrillation hospitalised with myocardial infarction in 2016-2023: timeliness of clinical guideline adherence - K. G. Pereverzeva; S. S. Yakushin; N. A. Kindyakova; P. R. Mamedov (Рациональная фармакотерапия в кардиологии)
Aim. To analyse the dynamics of prescribing triple antithrombotic therapy (TATT) at discharge (TATT: oral anticoagulant (OAC) + two antiplatelet agents) in patients with atrial fibrillation (AF) and acute myocardial infarction (MI) between 2016-2023, as well as the alignment of clinical practice with the clinical guidelines of the European Society of Cardiology (ESC) and the Russian Society of Cardiology (RSC).Material and methods. A retrospective analysis was conducted on 813 patients with AF and acute MI, divided into four groups based on hospitalisation period: 2016-2017 (n=104), 2018-2019 (n=256), 2020-2021 (n=239), 2022-2023 (n=214). The frequency and composition of ATT prescriptions were assessed, along with their compliance with current guidelines. Due to the absence of RSC guidelines before 2020, ATT compliance was assessed against the 2015 ESC guidelines for non-ST-segment elevation acute coronary syndrome (NSTE-ACS), the 2017 ESC guidelines for ST-segment elevation myocardial infarction (STEMI), and the 2016 ESC guidelines for AF. After 2020, compliance was evaluated against the 2020 RSC guidelines for the same conditions.Results. Among patients not undergoing percutaneous coronary intervention (PCI), OAC + antiplatelet therapy was prescribed to 10.2% in 2016-2017 and 13.5% in 2018–2019, aligning with the 2016 ESC guidelines for AF. Among PCI-treated patients, TATT was prescribed in 9.1% of cases in 2016-2017 and 51.0% in 2018-2019, consistent with ESC guidelines. In non-PCI patients, the correct OAC + antiplatelet combination was prescribed to 17.2% in 2020-2021 and 27.5% in 2022-2023. TATT at discharge was prescribed to 48.7% of PCI-treated NSTE-ACS patients in 2020-2021 and 72.5% in 2022-2023, aligning with the 2020 RSC guidelines for NSTE-ACS. The combination of OAC + antiplatelet therapy for PCI-treated STEMI patients was prescribed in 13.3% of cases in 2020-2021 and 8.6% in 2022-2023, consistent with the 2020 RSC guidelines for STEMI. Overall, OAC use increased from 16.3% in 2016-2017 to 87.9% in 2022-2023.Conclusion. The study demonstrates significant progress in OAC and TATT prescription. However, a gap remains between clinical practice and guidelines, particularly in the composition of combination therapy at discharge.